2002
DOI: 10.1002/glia.10134
|View full text |Cite
|
Sign up to set email alerts
|

The tetraspanin protein, CD9, is expressed by progenitor cells committed to oligodendrogenesis and is linked to β1 integrin, CD81, and Tspan‐2

Abstract: Previous studies identified the tetraspanin protein CD9 in myelinating oligodendrocytes. The present report extends these observations by identifying CD9 in a subpopulation of oligodendrocyte progenitor cells (OPCs) and in premyelinating oligodendrocytes in rodents. NG2-positive cells expressed CD9 in a temporal and spatial pattern during development that was consistent with CD9 expression in OPCs just prior to their differentiation into premyelinating oligodendrocytes. NG2-positive cells in mature brains were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 19 publications
3
77
0
1
Order By: Relevance
“…These mice are healthy except for sperm-egg fusion. The life span of these mutants is normal, and for the nervous system, Terada et al (2002) reported that oligodendrocyte production and myelination appear normal in this mutant. To examine the fine structure of the myelin membrane, we performed ultrastructural analyses on optic nerves from wild-type and CD9-deficient mice (Miyado et al, 2000) at 8 weeks of age.…”
Section: Lack Of Cd9 Causes Disruption Of the Paranodal Junction In Tmentioning
confidence: 92%
See 1 more Smart Citation
“…These mice are healthy except for sperm-egg fusion. The life span of these mutants is normal, and for the nervous system, Terada et al (2002) reported that oligodendrocyte production and myelination appear normal in this mutant. To examine the fine structure of the myelin membrane, we performed ultrastructural analyses on optic nerves from wild-type and CD9-deficient mice (Miyado et al, 2000) at 8 weeks of age.…”
Section: Lack Of Cd9 Causes Disruption Of the Paranodal Junction In Tmentioning
confidence: 92%
“…It is possible that myelination is terminated by CD9 together with some other molecules, including integrins and extracellular matrix proteins. Because CD9 interacts with several molecules, including the ␤ 1 integrin subfamily (Nakamura et al, 1995;Berditchevski et al, 1996;Schmidt et al, 1996;Terada et al, 2002), and because Schwann cells express ␤ 1 integrin (Salzer, 1995), ␤ 1 integrin is one of the candidates for this function. The ␤ 1 integrin subfamily comprises heterodimeric transmembrane proteins that mediate cell adhesion to extracellular matrix proteins, including laminin (␣ 3 ␤ 1 , ␣ 6 ␤ 1 ), collagen (␣ 1 ␤ 1 , ␣ 2 ␤ 1 , ␣ 3 ␤ 1 ), and fibronectin (␣ 4 ␤ 1 , ␣ 5 ␤ 1 ) (Hynes, 1992).…”
Section: Cd9 May Act As the Terminal Signal Of Myelination In The Pnsmentioning
confidence: 99%
“…Antibody 2166 was raised in rabbits against an epitope of Tspan-2, an oligodendrocyte-specific tetraspanin protein of 25 kDa (Birling et al, 1999;Terada et al, 2002). The original intention was to use this antibody to map oligodendrocyte disposition and lineage in the brain.…”
Section: Antibody Stains Nmj-capping Cellsmentioning
confidence: 99%
“…Protein Rab GDP dissociation inhibitor alpha (GDI1), dihydropyrimidinaserelated protein 2 (DPYSL2 -CRMP-2), PLP1, thioredoxin (TXN), MAG, MBP, CD9 antigen (CD9), alpha-synuclein (SNCA), tubulin beta-3 chain (TUBB3), and protein NDRG1 (NDRG1) were found to be downregulated at proximal and distal stumps in the presence of NGF, and in the presence of rapamycin, the expression of these proteins was downregulated at distal stumps of nerves, but were normalized in the proximal stumps. These proteins regulate nervous system development, axonogenesis, glial cell differentiation, myelination, and myelin maintenance [107][108][109][110][111][112][113][114][115]. Results of ANOVA also showed that many proteins involved in apoptosis ( Figure 21) were regulated differentially in the sciatic nerve 4 weeks after injury.…”
Section: Resultsmentioning
confidence: 94%